Impacto en el consumo y comportamiento de compra de las familias orenses generado por la crisis sanitaria. - Muñoz Chamba, Joel Andre; Vera Vega, Leslie Krisbel (My University, 2022)
The economy has been one of the sectors most affected by the global health emergency, resulting in an increase in unemployment and poverty rates, reducing purchasing power and affecting household consumption and purchasing behavior. The main objective of this article is to analyze the consumption and purchasing behavior of families in the province of El Oro during the COVID-19 health emergency. The research presents a descriptive approach, which was carried out through statistical databases, bibliographic sources and articles in specialized magazines. The instrument used to collect the information was the survey; Questionnaire consisting of 18 questions, addressed to 383 families from Ourense. The data obtained allowed us to know the impact of the health crisis on families from Ourense, households that experienced variations in consumption and purchasing behavior due to the decrease in their income, job losses and economic instability.
La economía ha sido uno de los sectores más afectados por la emergencia sanitaria a nivel global, dejando como resultado un incremento en las tasas de desempleo y pobreza, reduciendo el poder adquisitivo e incidiendo en el consumo y comportamiento de compra de los hogares. El presente artículo tiene como objetivo principal analizar el consumo y comportamiento de compra de las familias de la provincia de El Oro durante la emergencia sanitaria del COVID-19. La investigación presenta un enfoque descriptivo, el cual se llevó a cabo mediante bases de datos estadísticos, fuentes bibliográficas y artículos en revistas especializadas. El instrumento empleado para recolectar la información, fue la encuesta; cuestionario que consta de 18 preguntas, dirigida a 383 familias orenses. Los datos obtenidos permitieron conocer el impacto de la crisis sanitaria en las familias orenses, hogares que experimentaron variaciones en el consumo y comportamiento de compra debido a la disminución de sus ingresos, pérdidas de empleo e inestabilidad económica.
Keywords: CONSUMO; CRISIS SANITARIA; INGRESOS; DESEMPLEO